Endothelial Nitric Oxide Synthase Gene Polymorphisms and Risk of Preeclampsia - Qi, Hui-Ping; Fraser, William D.; Luo, Zhong-Cheng; Julien, Pierre; Audibert, Francois; Wei, Shu-Qin (American Journal of Perinatology, 2013)
Polymorphisms in endothelial nitric oxide synthase (eNOS) gene may affect the risk of preeclampsia. This systematic review aimed to provide an updated review of the literature to better understand the association between the eNOS gene polymorphisms and the risk of preeclampsia. We searched electronic databases of the human literature in PubMed, EMBASE, and the Cochrane Library up to July 2012. A meta-analysis was conducted on the association of eNOS G894T, T786C, and intron 4b/a polymorphisms with preeclampsia using (1) allele contrast, (2) recessive, (3) dominant, and (4) additive models. Thirty-three studies comprising 10,671 participants met the inclusion criteria. There was statistically significant association between the G894T variant and increased risk of preeclampsia (TT versus TG + GG: odds ratio 1.43, 95% confidence interval: 1.13 to 1.82). However, no significant risk of preeclampsia was observed either in the T786C or the intron 4b/a polymorphism. Homozygosity TT in eNOS G894T variant is significantly associated with an increased risk of preeclampsia.
Keywords: preeclampsia; endothelial nitric oxide synthase; polymorphism